2023
DOI: 10.1111/nph.19115
|View full text |Cite
|
Sign up to set email alerts
|

Experimental warming altered plant functional traits and their coordination in a permafrost ecosystem

Abstract: Summary Knowledge about changes in plant functional traits is valuable for the mechanistic understanding of warming effects on ecosystem functions. However, observations have tended to focus on aboveground plant traits, and there is little information about changes in belowground plant traits or the coordination of above‐ and belowground traits under climate warming, particularly in permafrost ecosystems. Based on a 7‐yr field warming experiment, we measured 26 above‐ and belowground plant traits of four domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…In this context, some manipulated experiments have also demonstrated that increased precipitation has no significant effects on soil nutrient availability and community biomass in alpine meadows of the Tibetan Plateau (Hu et al, 2022;Zhang et al, 2017Zhang et al, , 2019. By contrast, increased temperature significantly enhances plant community biomass and leaf nutrient concentrations in the meadows of the Tibetan Plateau, indicating an increase in soil nutrient availability by elevated temperature (Wei et al, 2023;. We observed that soil water and nutrient availability in the three sites of our study did not change in a coordinated manner but rather varied independently (Figure S6a,b).…”
Section: Decoupling Of the Cortical And Stelar Traits In Absorptive R...mentioning
confidence: 99%
“…In this context, some manipulated experiments have also demonstrated that increased precipitation has no significant effects on soil nutrient availability and community biomass in alpine meadows of the Tibetan Plateau (Hu et al, 2022;Zhang et al, 2017Zhang et al, , 2019. By contrast, increased temperature significantly enhances plant community biomass and leaf nutrient concentrations in the meadows of the Tibetan Plateau, indicating an increase in soil nutrient availability by elevated temperature (Wei et al, 2023;. We observed that soil water and nutrient availability in the three sites of our study did not change in a coordinated manner but rather varied independently (Figure S6a,b).…”
Section: Decoupling Of the Cortical And Stelar Traits In Absorptive R...mentioning
confidence: 99%
“… Wei et al (2023). show that within-species phenotypic plasticity of dominant understory species, rather than species turnover, alters the community-level traits in a warming experiment.…”
mentioning
confidence: 95%
“…Warming can increase air and soil temperature, leading to a reduction in soil moisture, which in turn affects plant photosynthetic capacity and LUE ( Forkel et al., 2016 ; Allison et al., 2018 ). Warming also caused a shift in plant functional traits, leading to an increase in acquisitive characteristics such as larger leaves, higher photosynthetic resource-use efficiency, thinner roots, and greater specific root length and nutrient concentrations ( Wei et al., 2023 ). Yao et al.…”
Section: Introductionmentioning
confidence: 99%
“…(2022) , experimental warming did not alter the content of soil organic carbon (SOC) during the growing season in an alpine meadow. Wei et al. (2023) demonstrated that plants exhibit consistent adaptive strategies in both above- and belowground traits, favoring more acquisitive traits in warmer environments.…”
Section: Introductionmentioning
confidence: 99%